A high-strength Mg-8Zn-1Mn-3Sn-1.2Gd alloy with fine MgSnGd particles by Dy modification. (August 2022) - Zhou, Yang; Xue, Hansong; Peng, Jianbo; Pan, Haitao; Xie, Wei; Liu, Song; Zhang, Dingfei; Jiang, Bin; Pan, Fusheng
Graphical abstract: Highlights: A new phase MgSn (Gd, Dy) is formed and its effect on MgSnGd particles are clarified. The modified MgSnGd phase promote dynamic recrystallization process. Achieving the excellent comprehensive mechanical properties of ZMT813-1.2Gd-0.2Dy alloy. Abstract: In the current work, we successfully prepared Mg-8Zn-1Mn-3Sn-1.2Gd-0.2Dy alloy with an excellent combination of ultimate tensile strength and ductility. The mechanism of the Dy-modified MgSnGd phase and its effect on the microstructure and mechanical properties of as-cast and as-extruded alloy were systematically investigated. Experimental results reveal that a new phase MgSn (Gd, Dy) is formed with Dy addition to Mg-8Zn-1Mn-3Sn-1.2Gd alloy, MgSn (Gd, Dy) phase can act as an effective heterogeneous nucleation site of MgSnGd phase. Meanwhile, the addition of Dy consumes Sn and Gd atoms, reducing the enrichment of solute atoms and inhibiting the MgSnGd phase's growth. The Dy addition can effectively promote the dynamic recrystallization process due to the combined effects of the refined grain structure of as-cast alloy and the particle-stimulated nucleation effect caused by dispersed MgSnGd phase. The alloy exhibits an excellent combination of high strength and ductility with the ultimate tensile strength of 384 MPa and an elongation of 14.5%. The fine-grained structure, the uniformly distributed MgSnGd particle, and MgSn (Gd, Dy) nanoparticles are mainly responsible for the ultra-high ultimate tensile strength. The high ductility is due to the fine-grained structure, appropriate decrease of dislocation density, and dynamic recrystallization.